Trabalho na agroindustria rural e política de expansão do ensino profissionalizante e tecnológico: a empregabilidade na microrregião de Ituiutaba de 2008 a 2015 - Tano, Cleide Francisca de Souza (2016)
This research aims to carry out an analysis of the relationship between the policy of vocational and technological education expanded to microregion of Ituiutaba and, in turn, discuss the employability in the agroindustry of the graduates of the Technical Course of Agribusiness integrated to high school of the Federal Institute of Education, Science and Technology of the Triângulo Mineiro - IFTM Campus Ituiutaba, in the period of 2008 to 2015. It presents analyzes of issues related to employability, vocational training and education, in the context of the policy of expansion of vocational and technological education. The specific objectives were: to understand what is the intentionality of the expansion of vocational and technological institutes; to analyze the insertion of graduates in the productive processes of rural areas, specifically in rural agribusiness of the microregion of Ituiutaba from 2008 to 2015; to investigate the interaction of IFTM with rural agro-productive sector of micro-Ituiutaba; and to verify the effectiveness of the policy for the training of qualified professionals, both for work and for social interaction and civic life. This research follows a Materialist Critique history perspective, and it was held in two stages: at first we conducted the bibliographical and documentary research and on a second moment the field research. The collected information correlated with the studied theoretical apparatus allow analysis and discussions on the theme: work in rural and vocational and technological education policy. It is aligned with the research line Work, Society and Education. The results and conclusions show that specifically in the case of graduates who answered the questionnaire, employability in rural agroindustry is almost non-existent, however, there is employability in other sectors and there are also graduates providing autonomous services. The results also point out that this policy flirts with two intentions: it prepares for the labor market and for access to higher education. On the part of the graduates, we perceive a denial of vocational and technological education as it is put, however, there is a search on the part of the graduates to take advantage of the best opportunity that they have available in the matter of education to enter higher education, even if they have to submit to practical classes and, along the way, it is perceived that many graduates change their perception on the practical and technical classes. Consequently, access to higher education by these graduates occurs in a much larger proportion than to employment. We believe that this research provides margins for other research on work, education, professional training in questions about the verification of the effectiveness of internalization, effectiveness of IFTM alignment with Local Productive Arrangements, amongst others. Thus, we expect to contribute to the production of knowledge and the debate on this subject as well as to assist in the analysis of historical data of the studied area, and also to contribute to the academic field in order to promote studies on the training policies and professional integration.